Pengembangan Materi Ajar Fisika Berbasis Google Sites Untuk Meningkatkan Keterampilan Kolaborasi Peserta Didik - A. Nurwina; Ahmad Yani; Muhammad Arsyad (Jurnal Penelitian Pendidikan IPA, 2025)
This research is a type of Research and Development (R&D) that implements the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). This study aims to develop physics teaching materials based on Google Sites and test their effectiveness in improving students' collaboration skills. The material trial was conducted on 29 grade XI students of SMAIT Darul Fikri Makassar. The instruments used included a physics teaching material validation sheet, a teacher assessment questionnaire, a student response questionnaire, and a validated collaboration skills test. The results of the study indicate that the development of physics teaching materials is theoretically conceptualized based on the principles of social constructivism learning, connectivism theory, and the principles of collaborative instructional design based on digital technology. Through product validation, the teaching materials are in the valid category with an average Aiken's V value of 0.85. Empirically, it demonstrates practicality with a teacher response percentage of 87.38% and a student response percentage of 76.86%, categorized as very practical. Meanwhile, effectiveness with an average N-Gain of 0.66 is categorized as moderate. Based on these results, the Google Sites-based physics teaching material is theoretically valid through expert assessment, empirically practical, and effective in improving collaboration skills in physics learning.